DEEP LEARNING IN ISLAMIC EDUCATION: A COMPARATIVE APPROACH OF JOHN DEWEY AND PAULO FREIRE’S EDUCATIONAL PHILOSOPHIES FOR TRANSFORMATIVE TEACHING - Nisaa Unzylayka (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study explores the conceptual integration of deep learning within Islamic Education through a comparative analysis of the educational philosophies of John Dewey and Paulo Freire. Responding to the growing challenge of technological disruption in education, the study argues that the implementation of deep learning should not be limited to technical or mechanistic approaches, but must be grounded in strong philosophical and ethical foundations. Using an interpretative qualitative method, this research employs comparative thematic analysis to examine key concepts such as experience, reflection, dialogue, critical consciousness, and social transformation in the works of Dewey and Freire. The findings reveal that Dewey’s pragmatic and democratic orientation toward experiential learning complements Freire’s critical and emancipatory pedagogy aimed at social justice. Their integration offers a transformative learning framework that aligns with the moral, spiritual, and social values of Islamic Education. This study contributes theoretically by formulating a conceptual model of deep learning that bridges pragmatic and critical perspectives, and practically by offering a value-oriented direction for educators in designing reflective, dialogical, and socially responsive learning environments. The proposed framework positions Islamic Education as a mediating force between technological advancement and humanistic educational transformation.